2002
DOI: 10.1038/sj.jea.7500215
|View full text |Cite
|
Sign up to set email alerts
|

Residential radon exposure and lung cancer: Variation in risk estimates using alternative exposure scenarios

Abstract: The most direct way to derive risk estimates for residential radon progeny exposure is through epidemiologic studies that examine the association between residential radon exposure and lung cancer. However, the National Research Council concluded that the inconsistency among prior residential radon casecontrol studies was largely a consequence of errors in radon dosimetry. This paper examines the impact of applying various epidemiologic dosimetry models for radon exposure assessment using a common data set fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Although this could conceivably be an artifact of the choice of administrative data boundaries, this finding may also be due to higher residential radon concentrations in the Northeast and other factors unaccounted for in the analysis including possible regional differences in time spent at home (53). Although there is no information on time-activity patterns for characterizing time spent at home for individuals in the CPS-II cohort, results from the U.S. National Human Activity Pattern Survey showed that time spent in a residence was consistent across all 10 regions of the United States (54).…”
Section: Discussionmentioning
confidence: 99%
“…Although this could conceivably be an artifact of the choice of administrative data boundaries, this finding may also be due to higher residential radon concentrations in the Northeast and other factors unaccounted for in the analysis including possible regional differences in time spent at home (53). Although there is no information on time-activity patterns for characterizing time spent at home for individuals in the CPS-II cohort, results from the U.S. National Human Activity Pattern Survey showed that time spent in a residence was consistent across all 10 regions of the United States (54).…”
Section: Discussionmentioning
confidence: 99%
“…18 -20 Epidemiologists maintain that the ecologic study design should be reserved for generating hypotheses rather than estimating risk. Our research group 13 and others 21 have argued that the lack of significant findings of some of the earlier residential case-control studies is attributable to random misclassification of risk factors, primarily from poor assessment of radon exposure, which reduces a study's power to detect an association.…”
Section: Rebuttalmentioning
confidence: 95%
“…These findings strongly suggest that previous radon studies may have actually underestimated the risk posed by residential radon, because exposure misclassification was found to bias the studies toward finding no association. 13 In summary, risk estimates from rigorously designed analytic epidemiologic studies provide compelling evidence that prolonged residential radon exposure increases the risk of lung cancer.…”
Section: Opening Statementmentioning
confidence: 99%
See 2 more Smart Citations